Structure and Mechanisms of Action of The Educational Cluster - Sh, Mardonov; S, Toshtemirova; B, Ahmadjonov; N, Koshanova (International Journal of Psychosocial Rehabilitation, 2020)
This article describes how to integrate types of education, the content and content of types of education based on innovation, as well as the implementation of innovative approaches to education. The main purpose of the study is also outlined. The educational cluster as an innovative approach is scientifically-pedagogically substantiated and effective mechanisms for its functioning are developed. The analysis of the results of foreign and domestic studies on the scientific foundations and mechanisms of the educational cluster. The object and subject of the study are described, the methods of activity are studied. The stages of creating a cluster, the characteristics of the educational cluster and the mechanisms of quality functioning are scientifically substantiated. The analysis of factors influencing the development of the innovative cluster of teacher education, as well as the ways and results of their solution at the experimental sites of the "School-Laboratory" is presented. On the theoretical and practical basis of the study, recommendations and conclusions are made.